The Role of Direct Compensation and Organizational Citizenship Behavior on Performance through Job Satisfaction as a Mediating Variable at the Social Service of Jember Regency - Kurniawan, Muhammad Sifak Beni; Nursaid, Nursaid; Martini, Ni Nyoman Putu; Qomariah, Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This study aims to analyze the effect of direct compensation and Organizational Citizenship Behavior (OCB) on employee performance with job satisfaction as a mediating variable. Data were taken from the Jember Regency Social Service with a sample of 181 respondents. The analysis method used was path analysis. The results showed that direct compensation and OCB had a positive and significant effect on job satisfaction. Direct compensation had a positive but insignificant effect on the performance of social assistants of the Family Hope Program. Job satisfaction was also proven to be a significant mediating variable between direct compensation and performance, as well as between OCB and the performance of social assistants.